Compact Dual Band-Reject Monopole Antenna for UWB Applications - Wang, Ping (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this letter, a compact planar ultrawideband (UWB) monopole antenna with excellent band-rejection characteristics is proposed for UWB communications applications. To achieve band-rejection filter property at the WiFi / WiMAX bands, two different types of slots: sloped open-ended Z-shaped slot and split rectangle ring slot on radiation patch, are introduced to form two stop-bands. The measured and simulated results show that the band-notched characteristics not only bring good rejection frequency, but also improved the skirt area in the band-notched frequency, and the proposed antenna has nearly omni-directional radiation pattern, moderate gain, and low cross-polarization level, which is suitable for UWB communication applications.